Discovery - Art Show Booklet - Aesculapian Society, Faculty of Medicine (Université d'Ottawa | University of Ottawa, 2016)
The Discovery booklet contains submissions from medical students that participated in the UOttawa Med 2016 Art Show.
Keywords: Humanities in Medicine